Batch versus Continuous Flow Performance of Supported Mono‐ and Bimetallic Nickel Catalysts for Catalytic Transfer Hydrogenation of Furfural in Isopropanol. Issue 16 (5th July 2018) - Wang, Yantao; Prinsen, Pepijn; Triantafyllidis, Konstantinos S.; Karakoulia, Stamatia A.; Yepez, Alfonso; Len, Christophe; Luque, Rafael
Abstract: Furfural takes an important position in hemicelluloses biorefinery platforms. It can be converted into a wide range of chemicals. One important valorization route is the catalytic hydrogenation. Whereas molecular hydrogen is mostly used in industrial hydrogenation processes, recent studies also showed that alcohols can be used as reductants from which hydrides can be transferred catalytically to furfural. This process is often assisted by the formation of significant amounts of side products, in despite of high yields to the hydrogenolysis product 2‐methylfuran. The present work explores the catalytic behavior in batch and continuous flow of mono‐ and bimetallic nickel catalysts supported on activated carbon for the catalytic transfer hydrogenation of furfural in isopropanol. Abstract : What a performance ! Mono‐ and bimetallic nickel‐based catalysts are compared in batch‐ and continuous flow mode for the catalytic transfer hydrogenation of furfural in isopropanol. The catalytic performance depends mostly on the reactions conditions.